NEGATIVE TRANSFER IN LITHUANIAN STUDENTS’ WRITING IN ENGLISH - Daukšaitė, Aurelija (Sustainable Multilingualism / Darnioji daugiakalbystė, 2023)
This research intends to find out whether Lithuanians studying English as a foreign language make certain mistakes because of the influence of their native language. It focuses on negative transfer in writing in English and is qualitative rather than quantitative. The article discusses the errors and illustrates them with examples that come from a corpus for which the data was obtained from 34 Moodle forum posts written by English B2 students, native speakers of Lithuanian who were in year one or year two of their studies in various study programmes but also studied English at Vytautas Magnus University as an obligatory subject. The students participated in this forum in October 2018 and reflected on the week of presentations they had recently had: they were asked to write what they liked or did not like in the presentations their colleagues had given in class, what went well and what did not, what they should improve in the future, etc. This study identified the types of errors (based on Camilleri, 2004) that occurred most frequently and their source (based on Camilleri, 2004; Brogan & Son, 2015). Most frequently the students made errors in the cases where there was a specific grammatical category in English, but it was non-existent in Lithuanian, while sometimes the source of errors was literal translation from the native language. The error analysis shows that in the English classroom specific attention should be given to the verb forms “is” and “are”, “was” and “were”, “has” and “have”, articles, collocations, tense agreement, quantifiers, the sentence structure of the English language and the importance of word meanings.